Determination of internal quantum efficiency in GaInN-based light-emitting diode under electrical injection: carrier recombination dynamics analysis. (14th February 2019) - Han, Dong-Pyo; Yamamoto, Kengo; Ishimoto, Seiji; Iwaya, Motoaki; Takeuchi, Tetsuya; Kamiyama, Satoshi; Akasaki, Isamu
Abstract: We proposed a method to determine the internal quantum efficiency (IQE) of GaInN-based light-emitting diode (LED). For the accurate determination thereof, we carefully reviewed a conventional carrier rate equation and then proposed a set of advanced formulae, which can comprehensively explain the carrier dynamics in a modern GaInN-based LED. Based on our proposed formula, this convenient method to determine the IQE is presented. Next, to identify the proposed carrier rate equations and recombination dynamics, we investigated carrier lifetime. We also discuss the physical origins of IQE degradation in a modern GaInN-based LED such as efficiency droop and green gap.